2016
DOI: 10.1002/rcm.7456
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic profiling of luteolin‐7‐O‐glucoside in rat urine, plasma, bile and feces after oral administration using ultra‐high‐performance liquid chromatography/quadrupole time‐of‐flight mass spectrometry

Abstract: RATIONALE: Luteolin-7-O-glucoside (L7G), the main bioactive ingredient of Chinese Lantern, has various biological functions, including anti-inflammatory and anti-oxidative activities. However, research on luteolin-7-O-glucoside has focused on the extraction, separation and biological activities of this natural product, whereas the metabolism of luteolin-7-O-glucoside in vivo is not fully understood. In order to explore the metabolic profile of luteolin-7-Oglucoside, we investigated its metabolites in plasma, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Compounds P10, P14, P16, P18, P23, P32, P33, P39, and P41 were confirmed by authentic standards and identified as hyperoside, rutin, isoquercitrin, astragalin, luteoloside, quercetin, luteolin, kaempferol, and isorhamnetin. And flavonoid glycosides were characterized according to form the prominent ion of [M+H‐162] + or [M+H‐146] + in their MS 2 spectra, indicating loss of glucose or rhamnose residue .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Compounds P10, P14, P16, P18, P23, P32, P33, P39, and P41 were confirmed by authentic standards and identified as hyperoside, rutin, isoquercitrin, astragalin, luteoloside, quercetin, luteolin, kaempferol, and isorhamnetin. And flavonoid glycosides were characterized according to form the prominent ion of [M+H‐162] + or [M+H‐146] + in their MS 2 spectra, indicating loss of glucose or rhamnose residue .…”
Section: Resultsmentioning
confidence: 99%
“…In other words, it was necessary to detect the chemical constituents and metabolites so as to clarify the effective ingredients and the possible metabolic pathways of TZQ-F in vivo. In addition, the in vivo components of the two major herbs (Lotus leaf and Mulberry leaf) were also investigated in previous studies, and 15 and 36 metabolites were identified, respectively [7,8]. These experiences were helpful for this experiment.…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…UPLC operates with 1.7 μm chromatographic particles and a fluid system capable of operating at pressures in the 6000–15000 psi range, which could provide better peak resolution and higher sensitivity and speed for complex mixture separation compared with conventional high‐performance liquid chromatography (HPLC) . In general, the UPLC technique is combined with high‐resolution mass spectrometry (HRMS) for metabolite identification in vitro or in vivo . Quadrupole time‐of‐flight mass spectrometry (QTOF‐MS), a HRMS technique, allows the generation of mass information with higher accuracy and precision for the identification of known or unknown compounds, which could provide candidate empirical formulae with a mass error of less than 5 ppm .…”
mentioning
confidence: 99%